Perlindungan Hukum bagi Korban yang Menggunakan Narkotika Cair di Indonesia - Setiyowati, Endang; Widjangkoro, Hanung (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This research, titled “Legal Protection For Victims Who Use Liquid Narcotics In Indonesia”. aims to provide a clearer understanding of the evolving forms and distribution methods of narcotics in Indonesia, including the increasing use of narcotics in liquid form, which poses the risk of accidental exposure to the public. The study examines the mechanisms of legal protection available for individuals unintentionally exposed to liquid narcotics by analyzing Law Number 35 of 2009 on Narcotics, its implementing regulations, as well as law enforcement practices in the field. The research adopts a normative juridical method, relying on library-based research through a review of legislation, legal doctrines, and other relevant legal materials. The analysis is further enriched by examining court decisions and ethical standards to obtain a comprehensive understanding of legal accountability and potential violations committed by law enforcement officers. The findings indicate that although the regulation recognizes the category of “victims of narcotics abuse,” its implementation often leads to criminalization due to difficulties in proving the element of lack of intent. Legal protection should instead be provided through a victimological approach, integrated assessment mechanisms, medical and social rehabilitation, as well as guarantees that victims will not be subjected to criminal sanctions as long as it can be proven that they had no intention of misusing narcotics.